Analysis and Detection of a Target Gas System Based on TDLAS & LabVIEW - Alorifi, F.; Ghaly, S. M. A.; Shalaby, M. Y.; Ali, M. A.; Khan, M. O. (Engineering, Technology & Applied Science Research, 2019)
This paper introduces detection techniques of target gas concentration based on infrared absorption spectrum method and the simulation of the gas detection system using LabVIEW. In this work, the harmonic detection is performed by wavelength modulation technique with a related frequency signal to cover the measured signal and get the gas absorption coefficient that can be analysed to give a gas concentration. A series of simulations are carried out to scan weak absorption lines and extract the second harmonic curve of the absorption spectrum of the target gas. The absorption and second harmonic curves are acquired by changing the parameters of the target gas concentration and line width. This work claims to be a contribution to the study and the comprehension of gas detection system based on tunable diode laser absorption spectroscopy and can serve as a basis for practical data acquisition.